Luck77
Answered

Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

simplify fully
2√3 x 3√8​


Sagot :

Answer: 12√6

Step-by-step explanation:

Given the expression;

2√3 * 3√√8

= (2*3) * (√3*√8)

= 6 * (√24)

= 6 * √4*6

= 6 * (2√6)

= (6*2)√6

= 12√6

Therefore, the simplified form of the expression is 12√6.